(untitled) (The Review of Diabetic Studies, 2024)
Background: Assessing the link between family perceptions of their needs and satisfaction with the Emergency Department (ED) in the Kingdom of Saudi Arabia (KSA) requires consideration of both universal factors affecting healthcare satisfaction and the unique cultural, social, and healthcare context in Saudi Arabia. Family dynamics and healthcare practices in KSA may influence how families perceive their needs and how satisfied they are with the care their loved ones receive in the ED. The aim of the study: To explore the association between family’s needs perception and satisfaction in relation to used emergency department. Design: A correlation descriptive research design was utilized. Sampling: A convenience sample of 100 family members was selected. Setting: This study was conducted at the emergency department of Al Noor Hospital, Makkah. Instruments: Two instruments of data collection were used. Assessment of emergency ill patients’ family needs using CCFNI, and family satisfaction questionnaire were involved. Results: A strong negative correlation between total family satisfaction score and emergency care family needs for support (p=0.002), assurance (p=0.001), proximity (p=0.001), and information (p<0.001). While a moderate negative was found, the need for comfort (p=0.05). The total CCFNI score had a strong negative correlation with family satisfaction score (p=0.002). Conclusion: Understanding the link between family perceptions of their needs and their satisfaction with ED care in KSA is crucial for improving the quality of emergency care. By taking into account cultural, social and healthcare system factors, hospitals can implement targeted strategies to enhance both family satisfaction and the overall ED experience. More than half of studied family had poor family satisfaction. Also, the proximity need was the higher importance need ranked followed by information, assurance, support, and finally comfort need. General characteristics of family may play a subordinate role. Recommendations: Addressing the unique needs of families in the ED setting in KSA, particularly around communication, emotional support, and involvement in care, can improve patient outcomes and foster a more patient- and family-centered approach to care.